2014
DOI: 10.1111/wrr.12209
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal uptake and organ distribution of silver from two different wound dressings in rats after a burn trauma

Abstract: Silver-containing wound dressings are an integral part of wound therapy in adult and pediatric burn patients. The antimicrobial effect of silver is well known and has been described in numerous studies. Side effects are rarely reported from silver-containing wound care products, even though systemic absorption of silver has been shown by elevated levels of silver in the blood of patients after silver exposure during wound therapy. This animal study investigated the silver levels of blood and in which organs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(49 reference statements)
2
14
0
Order By: Relevance
“…Second, large amount of particles might be lost through fecal material and some settle down in the aquaria. Several studies have also suggested the distribution of silver in tissue including skin, bone marrow, liver, spleen, kidney, heart, thyroid gland, adrenal gland, pancreases, brain and lymph node (Pfurtscheller et al 2014). Further these results are also comparable to Boudreau et al (2016) in the case of 13 weeks administrated Sprague-Dawley rats.…”
Section: Discussionsupporting
confidence: 69%
“…Second, large amount of particles might be lost through fecal material and some settle down in the aquaria. Several studies have also suggested the distribution of silver in tissue including skin, bone marrow, liver, spleen, kidney, heart, thyroid gland, adrenal gland, pancreases, brain and lymph node (Pfurtscheller et al 2014). Further these results are also comparable to Boudreau et al (2016) in the case of 13 weeks administrated Sprague-Dawley rats.…”
Section: Discussionsupporting
confidence: 69%
“…These results came with those of [44] in increasing silver concentration in brain at the end point 28 d of their experiment after single intravenous injection with 5 mg/kg of 20 and 200 nm Ag NPs . There is an essential evidence proposing that Ag NPs can pass the blood testis barrier BTB as the occurrence of silver in the tissue of testicles which confirmed by exposing animals to Ag NPs through different routs of administration [36], [49], [50] , in current study the maximum concentrations of Ag and ZnO were 9.57 ±0.43 and 48.45±0.39µg/gm after 60 and 30 min of injection respectively with slow rate of elimination over experimental time points. Table 3.…”
Section: Ag and Zno Nps Distributionsupporting
confidence: 72%
“…Complete reepithelialisation was observed between the 12th and 34th postoperative day (median 17⋅5 days). MRSA at DSWs was postoperatively confirmed in three patients (No 14,15,18) at the second and third dressing change. In two of these patients (No 14, 18), epithelialisation was delayed [34 days (No 14) and 26 days (No 18)].…”
Section: Group D: Patients With Mrsa At the Ulcer Sitementioning
confidence: 86%